Inflicting Death Penalty to Sexual Offenders: A Comparison between Indonesia and Saudi Arabia - Hardyanthi, Try; Akbar, M. Fabian; Akbar Napitupulu, Ichwan Rizky; Nirwana, Nia Prilia; Yasmin, Shaffa Aulia (Indonesian Comparative Law Review, 2021)
The case of sexual violence is increasing every year in Indonesia. The current prevailed penalties for perpetrators of sexual violence as stated in the Penal Code and the Child Protection Act are considered ineffective. The public then proposed that the perpetrators of sexual violence should be sentenced to death. The study aims to conduct a comparative study between Indonesia and Saudi Arabia in punishing sexual violence perpetrators. This study will look at how the death penalty is deemed appropriate to be applied for sexual offenders. It also explores the prevailed punishments by Saudi Arabian government for sexual violence cases. The study is normative research with employing comparative and statutory approaches. The study shows that sexual violence could be regarded as extraordinary crime as it meets particular conditions. Indonesia opens up the possibilities to punish the sexual offenders with the death penalty. However, Saudi Arabia on the other hand did not impose death penalty for sexual violence perpetrators but rather have a public humiliation as an alternative.